Tumbuh Kembang Dan Maturasi Tulang Pada Pasien Talasemia Beta-Hemoglobin E - Loes Sjahruddin (Jurnal Kedokteran Gigi Terpadu, 2019)
Background: Growth and development process consists of two different processes which are still related to each other. The growth process refers to quantitative changes which have a physical impact, whereas the development process refers to a qualitative and quantitative change which focuses on the fully grown structure, functions, including emotional and skill. Measurement of physical growth is one of the practical ways to assess the health situation of a child. One of the growth indicators that can be used to assess a child’s developmental growth is through skeletal maturation. Hemoglobin E beta-thalassemia is an important cause of childhood chronic disease. The objective of this study was to obtain the image of physical growth and skeletal maturation in HbE thalassemia patients aged 9 to 14 years. Materials and Methods:  This was a descriptive study with a cross-sectional design, implemented in  HbE β thalassemia patients of 9-14 years of age. Results: From 78 children participated in the study, children with HbE β thalassemia showed a retard growth of vertebrae compared to control group.Conclusion:Retard of physical growth and skeletal maturation is apparent in HbE thalassemia patients.